Persepsi Mahasiswa Tentang Kualitas Pelayanan Costumer Service Dan Fasilitas Bank Jateng Syariah Cabang Pembantu Universitas Muhammadiyah Surakarta Terhadap Kepuasan Mahasiswa Program Studi Pendidikan Akuntansi Dalam Melakukan Registrasi Akademik - Noviana, Marlia, Dr. Sabar Narimo, MM, M.Pd (2017)
The purpose of this research are: 1) To determine the influence of students' perceptions about the quality of service to student satisfaction. 2) To determine the effect of the facility to the students' perceptions of student satisfaction. 3) To determine the influence of students' perceptions about the quality of services and facilities to student satisfaction. This research is descriptive quantitative research with a conclusion through statistical methods. The population in this study were all students of Accounting Education, samples taken as many as 243 students with proportional random sampling. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, t-test, F, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 7.652 + 0.400 + 0.591 X1 X2. The equation shows that student satisfaction is influenced by the quality of service and facilities. The conclusions drawn are: 1) The perceptions of students about the quality of service to student satisfaction acceptable. This is based on multiple linear regression analysis (t test) note that > , 4.602> 1.960 and the significance value <0.05, namely 0.000 with relative contributions of 41% and the effective contribution of 18.9%. 2) Perception facility to the students about student satisfaction acceptable. This is based on multiple linear regression analysis (t test) note that > , namely 6.568> 1.960 and the significance value <0.05, namely 0.000 with the relative contribution of 59% and the effective contribution of 27.2%. 3) The perception of students about the quality of services and facilities to student satisfaction acceptable. This is based on multiple linear regression analysis of variance (F test) is known that > , ie 87.632> 3.000 and the significance value <0.05, namely 0.000. 4) The coefficient of determination (R2) of 0.461 indicates that the influence of students' perceptions about the quality of services and facilities to the satisfaction of the students was of 46.1%, while the rest influenced by other variables.